Predictors of Successful Learning in Multilingual Older Adults Acquiring a Majority Language - Blumenfeld, Henrike K.; Quinzon, Sim J. R.; Alsol, Cindy; Riera, Stephanie A. (Frontiers in Communication, 2017)
Understanding language learning in later life can elucidate how linguistic experiences and age-specific cognitive skills can be leveraged for language acquisition, providing insight into how lifelong experiences configure our learning capacity. In this study, we examined to what extent acquisition and maintenance of a non-native language (English) is scaffolded by cognitive skills and previous linguistic experiences in older adults; and to what extent these cognitive/linguistic factors predict older learners’ success in acquiring novel functional language. We recruited 53 participants who were native speakers of Mandarin, Spanish, Tagalog and Somali, had continued to learn English as adults, and were currently exposed to majority-English contexts. To identify contributors to participants’ English skills, we administered a language history and self-reported proficiency interview, brief cognitive testing, and verbal fluency tasks in L1 and English. We found that digit span and orientation measures were cognitive predictors of English proficiency, while similarity of known languages to English, L1 skills, and English language exposure were linguistic predictors of English skills. To examine participants’ ability to maintain language knowledge and to learn new functional English, we also conducted a preliminary longitudinal service-based study in a subset of 19 participants using our Specific-Purpose English Communication System for Seniors (SPECSS) curriculum. In this subset of SPECSS learners, we identified digit span and orientation, but not age, as cognitive predictors of short-term language maintenance and new language learning success. Further, better novel English learning as a result of our curriculum was observed in learners whose other known languages were less similar to English. Findings inform best practices in developing language curricula for older adults, and help generate new hypotheses on preparedness for language learning across the adult lifespan with a possible interaction between cognitive skills and transfer of knowledge from previous languages in multilingual older learners.